2014
DOI: 10.1007/s13277-014-2987-5
|View full text |Cite
|
Sign up to set email alerts
|

ALCAM is indirectly modulated by miR-125b in MCF7 cells

Abstract: MicroRNA (miRNA) deregulation is associated with various cancers. Among an expanding list of cancer-related miRNAs, deregulation of miR-125b has been well documented in many cancers including breast. Based on current knowledge, miR-125b is considered to be a tumor suppressor in breast cancers. While important messenger RNA (mRNA) targets have been defined for miR-125b, here, we aimed to further investigate direct/indirect consequences of miR-125b expression in breast cancer cells by using a transcriptome appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…ALCAM was found to be one of a panel of genes whose expression was altered following expression of miR-125b. Expression of miR-125b enhanced both ALCAM mRNA and protein levels, which was found to influence MCF-7 growth using a further shRNA study [122]. It has also recently been reported that inhibition of miR-214, overexpression of miR-148b or a combination can inhibit tumour cell crossing of the vessel endothelium through a negative regulation of ALCAM and integrin α5 [123].…”
Section: Metastatic Potential Of Alcam and Clinical Implications In Bmentioning
confidence: 73%
“…ALCAM was found to be one of a panel of genes whose expression was altered following expression of miR-125b. Expression of miR-125b enhanced both ALCAM mRNA and protein levels, which was found to influence MCF-7 growth using a further shRNA study [122]. It has also recently been reported that inhibition of miR-214, overexpression of miR-148b or a combination can inhibit tumour cell crossing of the vessel endothelium through a negative regulation of ALCAM and integrin α5 [123].…”
Section: Metastatic Potential Of Alcam and Clinical Implications In Bmentioning
confidence: 73%
“…MicroRNAs (miRNAs, miRs) are a class of small non-coding RNA that regulates gene expression by targeting the 3' untranslated region (UTR) of targeted mRNAs (7)(8)(9). Previous studies indicated that the abnormal expression of miRNA was involved in tumorigenesis with a tissue-specific expression pattern (6,7,10).…”
Section: Introductionmentioning
confidence: 99%